Penegakan Hukum dalam Era Reformasi - Abrar Saleng (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The law enforcement in the reform era has not been achievable even the trust of the public on law and the law enforcement tend to lower and lower. In the reform era public directly witness how poor the law and the judicature are going on. The up holder law still use the out of date paradigm but they use the new fashion.